2016
DOI: 10.1002/ecy.1536
|View full text |Cite
|
Sign up to set email alerts
|

Chemical similarity and local community assembly in the species rich tropical genus Piper

Abstract: Community ecologists have strived to find mechanisms that mediate the assembly of natural communities. Recent evidence suggests that natural enemies could play an important role in the assembly of hyper-diverse tropical plant systems. Classic ecological theory predicts that in order for coexistence to occur, species differences must be maximized across biologically important niche dimensions. For plant-herbivore interactions, it has been recently suggested that, within a particular community, plant species tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 65 publications
(101 reference statements)
7
86
1
Order By: Relevance
“…However, our analyses tend to suggest that the average phylogenetic distance among co-occurring species of a given genus may depend simply on the age of the genus, although the exact phylogenetic distance estimates will depend on how well the genus has been sampled phylogenetically. Furthermore, the high degree of sympatric co-occurrence observed for the speciesrich genera studied here suggests that there might not be strong constraints on the number of co-occurring congeneric species, especially if they differ in terms of herbivore defense traits (42,44,45). One of the key factors influencing the number of co-occurring species of a given genus in a given Amazonian tree community may simply be the total diversity of that genus in the Amazon, because dispersal into regions, which provide species for local communities, does not seem to be limited (46).…”
Section: Discussion Primacy Of Historical Dispersal In the Assembly Omentioning
confidence: 99%
“…However, our analyses tend to suggest that the average phylogenetic distance among co-occurring species of a given genus may depend simply on the age of the genus, although the exact phylogenetic distance estimates will depend on how well the genus has been sampled phylogenetically. Furthermore, the high degree of sympatric co-occurrence observed for the speciesrich genera studied here suggests that there might not be strong constraints on the number of co-occurring congeneric species, especially if they differ in terms of herbivore defense traits (42,44,45). One of the key factors influencing the number of co-occurring species of a given genus in a given Amazonian tree community may simply be the total diversity of that genus in the Amazon, because dispersal into regions, which provide species for local communities, does not seem to be limited (46).…”
Section: Discussion Primacy Of Historical Dispersal In the Assembly Omentioning
confidence: 99%
“…For example, Rasmann and Agrawal () showed that the expression of secondary metabolites in Asclepias is associated with both the ecology and the phylogenetic position of the species. However, only a weak phylogenetic signal of leaf secondary chemicals was found for the genus Piper (Salazar, Jaramillo, & Marquis, ) and for the tropical species in the genus Inga (Kursar et al, ), both cases where co‐occurring species tend to diverge in chemical composition. Hence, whether plant chemical profiles have a strong phylogenetic signal and whether the latter is stronger than the signal from physical traits remain to be evaluated across systems.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites are one of the most effective defences plants have against insect herbivores, and play a central role in shaping both ecological and evolutionary interactions. For example, the high local diversity of trees in tropical rainforests may be maintained, not because coexisting species differ in their abiotic niches (Kraft, Valencia, & Ackerly, ; Sedio, Wright, & Dick, ; Wright, ), but because they differ in their secondary metabolites, and therefore do not share herbivores (Coley & Kursar, ; Endara et al, ; Kursar et al, ; Salazar, D., Jaramillo, A., & Marquis, R. J., ; Salazar, D., Jaramillo, M. A., & Marquis, R. J., ; Vleminckx et al, ). Because there appear to be an infinite number of chemical combinations, this translates into an infinite number of niches with respect to herbivore pressure.…”
Section: Introductionmentioning
confidence: 99%